2018
DOI: 10.1136/thoraxjnl-2017-211138
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilisation and costs of home mechanical ventilation

Abstract: For HMV users, most healthcare costs were publicly supported or associated with family caregiving. Highest costs were incurred by the most dependent users. Understanding healthcare costs for HMV users will inform policy decisions to optimise resource allocation, helping individuals live at home while minimising caregiver burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…TPPV creates a major burden for caregivers in Switzerland because options for long-term care of ventilator-dependent tracheotomized patients outside the hospital are limited and financial support for qualified help at home is often insufficient. Healthcare costs for patients with chronic respiratory failure are far higher for invasive than for non-invasive ventilation [220]. Management of patients on invasive ventilation usually requires 24-h care.…”
Section: Special Situationsmentioning
confidence: 99%
“…TPPV creates a major burden for caregivers in Switzerland because options for long-term care of ventilator-dependent tracheotomized patients outside the hospital are limited and financial support for qualified help at home is often insufficient. Healthcare costs for patients with chronic respiratory failure are far higher for invasive than for non-invasive ventilation [220]. Management of patients on invasive ventilation usually requires 24-h care.…”
Section: Special Situationsmentioning
confidence: 99%
“…Few studies examine the cost of home mechanical ventilation. In a recent Canadian study, however, the overall median monthly healthcare cost with invasive ventilation was €6,200 across all diagnoses with the highest cost in ALS (range: €6,031-12,471) [35]. In a Norwegian, context the presence of professional carers in the patient's home around the clock would incur yearly costs in excess of €500,000, which would be covered by public funds.…”
Section: Justicementioning
confidence: 97%
“…Limited data are available on health care costs for HMV patients; higher costs are associated with more severe disease [97] and with the use of HMV in patients with ALS [33]. Indeed, a recent Canadian study found that 39% of the monthly health care costs was due to caregiving time provided by family members [98]. In this regard, home care programs meeting patient’s specific needs would be desirable to avoid the cost of respiratory assistance and of chronic care.…”
Section: Home Care Management Of Long-term Noninvasive Ventilationmentioning
confidence: 99%